Pengaruh Populasi Kutu Daun pada Tanaman Cabai Besar (Capsicum Annuum L.) terhadap Hasil Panen - ANGGRAINI, KORI’; YULIADHI, KETUT AYU; WIDANINGSIH, DWI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.1, Januari 2018, 2018)
The influence of the population of Aphids on crops of great chili pepper (Capsicum annuum L.) Against The Harvest One of the obstacles in the cultivation of pepper plants is the presence of aphid pest attack. The purpose of this research is to know the influence of the population of aphids on crops of Chili with different age and influence pest aphids attack against crops plant chili. Moving on to the results was showing that aphid pests attacked chili plants at different ages. The attack was found since the 100plant was two weeks after planting (wap) with the amount of 45.1 tail. Peak attacks occur in plants four weeks after planting (wap) with a total of 175.0 tails. Furthermore, the attack was a decrease due to the age of the plant getting older. An aphids attack results in low yields. Observation on chili harvest was done only 2 times. The highest occurrence of pepper crops has the lowest average yield of 33.8 g and 38.2 g whereas, the lowest pest-infected pepper plant has the highest average yield of 52.33 g and 57.2 g.